The role of leadership learning in the developmental needs of the senior managers in a rural municipality : a case study in adult education at Bushbuckridge local municipality - Mkhabela, Lamson Zondiwe (Stellenbiosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.